A Rapidly Enlarging Squamous Inclusion Cyst in an Axillary Lymph Node following Core Needle Biopsy - Cunxian Zhang; Jinjun Xiong; M. Ruhul Quddus; Joyce J. Ou; Katrine Hansen; C. James Sung (Case Reports in Pathology)
A 73-year-old woman was found to have a 1.7 cm axillary mass, for which a core needle biopsy was performed. The specimen revealed fragmented squamous epithelium surrounded by lymphoid tissue consistent with a squamous inclusion cyst in a lymph node, but a metastatic squamous cell carcinoma could not be excluded. Within one month, the lesion enlarged to 5 cm and was excised. Touch preparation cytology during intraoperative consultation displayed numerous single and sheets of atypical epithelioid cells with enlarged nuclei and occasional mitoses, suggesting a carcinoma. However, multinucleated giant cells and neutrophils in the background indicated reactive changes. We interpreted the touch preparation as atypical and recommended conservative surgical management. Permanent sections revealed a ruptured squamous inclusion cyst in a lymph node with extensive reactive changes. Retrospectively, the atypical epithelioid cells on touch preparation corresponded to reactive histiocytes. This is the first case report of a rapidly enlarging ruptured squamous inclusion cyst in an axillary lymph node following core needle biopsy. Our case demonstrates the diagnostic challenges related to a ruptured squamous inclusion cyst and serves to inform the readers to consider this lesion in the differential diagnosis for similar situations.